2020
DOI: 10.3390/ijerph17103584
|View full text |Cite
|
Sign up to set email alerts
|

Are Community Gardening and Horticultural Interventions Beneficial for Psychosocial Well-Being? A Meta-Analysis

Abstract: Recent literature has revealed the positive effect of gardening on human health; however, empirical evidence on the effects of gardening-based programs on psychosocial well-being is scant. This meta-analysis aims to examine the scientific literature on the effect of community gardening or horticultural interventions on a variety of outcomes related to psychosocial well-being, such as social cohesion, networking, social support, and trust. From 383 bibliographic records retrieved (from 1975 to 2019), seven stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 48 publications
3
48
0
1
Order By: Relevance
“…Mediation variables could intervene, such as physical activity carried out in private green spaces that would lead to relevant mental health benefits ( Dadvand et al, 2016 ). Likewise, we did not consider the potential mediating effect of gardening activities in private green spaces, which has been proven to generate benefits on health and well-being ( Clatworthy et al, 2013 ; Spano et al, 2020b ; Yeo et al, 2020 ). Further studies addressing these matters are strongly recommended.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%
“…Mediation variables could intervene, such as physical activity carried out in private green spaces that would lead to relevant mental health benefits ( Dadvand et al, 2016 ). Likewise, we did not consider the potential mediating effect of gardening activities in private green spaces, which has been proven to generate benefits on health and well-being ( Clatworthy et al, 2013 ; Spano et al, 2020b ; Yeo et al, 2020 ). Further studies addressing these matters are strongly recommended.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%
“…Previous studies focused on the subgroup analysis of the characteristics of activities and populations [23][24][25][26], not on the environment. This study fills this gap and demonstrates that non-hospital environments have a better therapeutic effect on all indicators than hospital environments.…”
Section: Outcomes and Processes Of Horticultural Therapymentioning
confidence: 99%
“…Meta-analyses can also be used to draw new conclusions from previous studies by investigating the different impacts of different conditions and dividing the studies into subgroups. Previous studies with different research foci can be further divided into several subgroups according to the type of activity (participatory horticultural therapy and ornamental horticultural activities [23]; horticultural intervention and community gardening [24]; raising plants, plant decoration, and combination activities [25]), participants (gardeners and non-gardeners [24,26] and different age groups [25]), country (U.S., U.K., and Asia [24]), respondents (patients or non-patients [26]), gardening (therapy vs. nontherapy [26]), subject types (child, teenager, adult, or elderly [26]), etc. Overall, these studies focused on the characteristics of activities and populations.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that one of the key resources that flow from shared social identities and group memberships are social support exchange opportunities, that is, interaction contexts for receiving, giving, and benefit from both social actions [ 5 , 24 , 25 ]. Empirical evidence in different contexts revealed that receiving social support was generally beneficial for psychosocial health [ 26 , 27 , 28 , 29 , 30 ], although there were some inconsistent results [ 17 ], and also that providing it might be even more beneficial than receiving it [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%